The Effects of Antidepressants on Neuropeptide Y in Patients with Depression and Anxiety - Ozsoy, S.; Olguner Eker, O.; Abdulrezzak, U. (Pharmacopsychiatry, 2016)
Introduction: This study aimed to investigate the neuropeptide Y (NPY) levels in patients with anxiety and depression and also the effects of antidepressants on this neuropeptide.Materials and Methods: The study included 40 outpatients who presented with depressive and anxiety symptoms, and 32 healthy controls. The patients received antidepressant treatment for 6 months. Serum levels of neuropeptide Y were measured before treatment in 40 patients, after 8 weeks of treatment in 32 patients, after 6 months in 10 patients, and once in the controls.Results: Serum NPY levels were lower in the patients than in the controls. NPY levels were increased and normalized by antidepressant treatment. While there was no change in NPY levels in the patients using fluoxetine and sertraline for 8 weeks, an increase was found in patients using escitalopram and venlafaxine. Serum NPY levels were increased by treatment for 8 weeks in the patients with depression, but not in the patients with anxiety.Discussion: The findings suggest that NPY may be related to pathophysiology in depression and anxiety, and antidepressants influence NPY levels.
Keywords: depression; anxiety; antidepressant; neuropeptide y